Relationship of Homoeostasis with Pancreatitis and Homoeopathic Management (Homoeopathy for All, 2025)
Homoeostasis is very much  important for the maintenance of  hormonal balance, and normal  function of the human body to cope  up with the external environment and  relationship with the pancreatitis.  The main cause of pancreatitis is the  obesity and alcoholic which later  on causes the damage to beta cells  of islets of Langer’s which causes  diabetes mellitus and to prevent  the further development of disease,  homoeopathic medicine plays an  important role for the management  of cases.
Keywords: Homoeostasis; pancreatitis